Associations between the pupil light reflex and the broader autism phenotype in children and adults - Soker-Elimaliah, Sapir; Lehrfield, Aviva; Scarano, Samuel R.; Wagner, Jennifer B. (Frontiers in Human Neuroscience, 2023)
The pupil light reflex (PLR) is a well-studied index of autonomic functioning. Studies have found that autistic children and adults have slower and weaker PLR responses compared to non-autistic peers, suggesting lower autonomic control. Altered autonomic control has also been associated with increased sensory difficulties in autistic children. With autistic traits varying in the general population, recent studies have examined these questions in the broader population. The current study looked at the PLR in relation to individual differences in autistic traits in non-autistic children and adults, asking how differences in the PLR, a marker of neuronal response to light, could lead to variation in autistic traits, and how this might change across development. Children and adults completed a PLR task as a measure of sensitivity to light and autonomic response. Results showed that, in adults, increased levels of restricted and repetitive behaviors (RRB) were associated with a weaker and slower PLR. However, in children, PLR responses were not associated with autistic traits. Differences in PLR were also found across age groups, with adults showing smaller baseline pupil diameter and stronger PLR constriction as compared with children. The current study expanded on past work to examine the PLR and autistic traits in non-autistic children and adults, and the relevance of these findings to sensory processing difficulties is discussed. Future studies should examine the neural pathways that might underlie the links between sensory processing and challenging behaviors.